(untitled) (Bioscience Journal, 2022)
The carbonized rice husk (CRH) is an agro-industrial residue with great potential for use in mixtures with other substrates for the production of vegetable seedlings. Thus, the purpose of this study was to evaluate the effect of the addition of CRH to the commercial substrate for the production of greenhouse seedlings. The evaluated vegetables were lettuce, broccoli and mustard, cultivated in polystyrene foam (Styrofoam®) trays. Five treatments were evaluated: 100% of the commercial substrate (CS); 25% of CRH + 75% of CS; 50% of CRH + 50% of CS; 75% CRH + 25% CS; and 100% CRH, in a completely randomized design with twelve replicates. The substrates were evaluated for their physical and chemical characteristics. The morphometric evaluations were: number of leaves per plant, plant height, shoot fresh matter yield, root length, and shoot and root dry matter yield. The data were submitted to regression analysis, and the homogeneity of the variance between the experiments was confirmed by the Cochran test. With the addition of CRH to the substrate, there was an increase in total porosity and P content and a reduction in density, water holding capacity, cation exchange capacity, electrical conductivity, and N, K, S, Ca and Mg contents. The carbonized rice husk added to the commercial substrate is a viable alternative for the production of lettuce, broccoli and mustard seedlings. The quality of the vegetable seedlings was higher when there was a 25% CRH + 75% CS mixture.